PENGARUH NILAI PELANGGAN, INOVASI PRODUK DAN KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH BANK MUAMALAT INDONESIA CABANG MADIUN - Binti Mutafarida (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2017)
The development of sharia banking in Indonesia very rapidly grow up preceded by Bank Muamalat Indonesia and in 2013 ranked as the bank with the highest loyalty and the best among other sharia banking nationally. Bank Muamalat Indonesia branch of Madiun is one of the first branch in Madiun and currently has many competitors from other sharia banking. Based on this background, in this study take what factors affect the size of customer loyalty Bank Muamalat Indonesia branch of Madiun. Based on the result of research, it is found that the level of loyalty of customer of Bank Muamalat of Madiun branch is mostly influenced by product innovation with value of t test value obtained by t-count 2,493, while second factor is influenced by service quality with result of tcount 2,268. So the least influenced factor by the value of the customer is with value of 2.217. This research is a descriptive research method and associative / relationship, this matter to know the value of independent variable. While population of this research is funding customer of Bank Muamalat Indonesia branch of Madiun with amount of 22.196 customer by taking data using random sampling method as much as 108 customer.